RANCANG BANGUN GAME RPG DENGAN UNREAL ENGINE BERBASIS DESKTOP - Albert, Albert; Saragih, Saut Pintubipar (LPPM Universitas Putera Batam, 2021)
Game engines are so useful for academy research because game engine can make an environments for simulator and provide implement for AI (Artifact Intelligence). Unreal Engine is the best choice for simulation and unreal engine have so many useful tools. Game are a high of entertainment that is in great demand by the public and children. Even for industry there are already make an E-Sport tournament.